STRATEGI MASYARAKAT MUSLIM JAWA DALAM MEMPERTAHANKAN IDENTITAS DI TENGAH LINGKUNGAN HINDU: STUDI DI KABUPATEN JEMBRANA BALI - Fithrotunna Muqowwamatul Millah, Dwi Setianingsih (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
Muslim communities, both migrants and natives from Jembrana Regency, Bali, strive to maintain their identity as Muslims within a social environment where Hinduism is the majority religion. As a minority group, Muslims there have certain social boundaries with adherents of other religions. This study employs a qualitative method with an ethnographic approach, using observation and interviews with both migrant and native Muslim communities. The strategic location of Jembrana Regency, which is close to Java Island, enables flows of migration from Java, whose population is predominantly Muslim. This condition makes the number of Muslims in the area nearly comparable to the Hindu population, allowing Muslims to maintain their Islamic identity even though they live in a region that is not predominantly Islamic. Thus, Muslims are still able to preserve their identity and carry out religious activities as Muslims in general